Sprei Soulmate (Sutra Organik Super Lembut Anti Alergi) Motivasi Ikarinetti - Achmad Faisal; Doni Hardianto; Dwichwanto; Laila Septiana (J-ENSITEC, 2021)
Along with the times and the era of globalization, the human need for information is expanding, especially information technology. People's need for information at this time is very large, people demand speed and ease in accessing the information needed. This is very much in line with the development of information and communication technology, including social media, currently, social media is widely used by the Indonesian people for buying and selling online. The internet has an impact on the emergence of digital advertising trends where Micro, Small and Medium Enterprises (MSMEs) use digital media as a promotional and marketing medium, all digital marketing activities that are currently trending are using social media endorsements to build trust in brands or products that are branded. they wake up. During the COVID-19 pandemic, it had a widespread negative effect on society, thus demanding entrepreneurs to make creative innovations. The Ikarinetti online store has developed marketing with Shopee e-commerce and made bed linen innovation products with motivational words that can be an alternative solution to survive and continue to exist during the COVID-19 pandemic.